The Wonderful World of Accounting - Ross, Howard (Journal of Accounting Research, 1970)
It is a great pleasure to meet with a group such as this, devoted to-or at least interested in-the study of what is actually going on in the real world, with the object of drawing useful conclusions from the facts. In my opinion, as a useful way of spending one's time this compares favorably with the popular pastime of arm-chair pontification with total reliance on a sort of mystic inner guidance developed during a lifetime of defending the indefensible from assaults of change. Simulated cases studied in the classroom and business games on the computer are certainly good fun and, up to a point, are perhaps instructive. But I welcome the evidence of a growing concern with studying the actual facts, rather than even the most ingenious simulations thereof. In such areas as financial communication, we cannot (and I am sure will never be able to) match the controlled conditions which the chemist or physicist can often create in his lab for experimentation. This may be illustrated, in a simple-minded sort of way, by contrasting the control of heat in a lab experiment with the control of inflation in the economy. Presumably by controlling the flow of fuel, temperatures can be raised in a lab experiment absolutely predictably. However, while inflation is certainly closely related to money supply, the effect on prices of a given increase in money supply is nothing like so predictable. The price rise depends on many noneconomic factors-for in dealing with people, all sorts of political considerations inevitably enter the picture-and I sometimes wonder whether our difficulties in controlling inflation do not stem from the fact that we tend to think of inflation as an economic rather than as a political problem. Certainly in Canada, during World War II, we virtually halted inflation by appointing a Prices Czar who announced it was not to take place. A special case of course, but one which dramatically illustrates the principle. But if we cannot hope to match the controlled observations of the